Development Of Volleyball Sports Achievements In The Petrokimia Gresik Women'S Volleyball Club (Case Study of the Implementation Development Achievement Petrokimia Gresik Volleyball Club in East Java) - Eva Novitasari; Sugiyanto Sugiyanto; Sapta Kunta Purnama (Kazimierz Wielki University, 2019)
This study aims to determine the club's background, supporting resources for club coaching, supporting coaching resources, the process of implementing achievement training, facilities and infrastructure, and funding for the Petrokimia Gresik women's volleyball club. The research method used is a qualitative research method with a type of case study research. Data collection techniques using interviews (In-dept interview), participant observation (passive participation), and documentation. The data validity technique uses two triangulation techniques, namely data triangulation and method triangulation. Data analysis was carried out in four stages, namely: the stage of data collection, the data reduction stage, the data presentation stage, the stage of drawing conclusions. The results showed that the development of the game of volleyball was progressing and developing so that in 1990 the women's volleyball team of Petrokimia Gresik was formed. Competent human resources in the coaching process consist of 3 trainers, athletes and administrators with a classification of nationally licensed trainers. Exercises at PBV Petrokimia Gresik are carried out 6 times a week. The facilities and infrastructure of volleyball sports provided by Petrokimia Gresik are sufficient. Funding for coaching activities can be very sufficient, because Petrokimia Gresik is a state-owned enterprise that can finance all needs in the process of fostering the achievement of Petrokimia Gresik volleyball.